Texture Classification for 3D Urban Map. (7th June 2009) - Inatsuka Inatsuka, Hiroyuki Hiroyuki; Uchino Uchino, Makoto Makoto; Ueno Ueno, Satoshi Satoshi; Okuda Okuda, Masahiro Masahiro
Abstract : This paper proposes a method to control texture resolution for rendering large-scale 3D urban maps. Since on the 3D maps texture data generally tend to be far larger than geometry information such as vertices and triangles, it is more effective to reduce the texture by exploiting the LOD (Level of Detail) in order to decrease whole data size. For this purpose, we propose a new method to control the resolution of the texture. In our method we classify the textures to four classes based on their salient features. The appropriate texture resolutions are decided based on the classification resulsts, their rendered sizes on a display, and their level of importance. We verify the validity of our texture classification algorithm by applying it to the large-scale 3D urban map rendering.